ESTIMATES OF HERITABILITY COEFFICIENTS FOR GROWTH TRAITS OF DJALLONKE SHEEP REARED ON THE STATE FARM OF BETECOUCOU IN BENIN - SENOU, MARCEL WANIGNON (My University, 2018)
This paper aims to estimate the coefficients of heritability of growth traits in Djallonke sheep. The data on growth (birth weight, the weight at 90 days and at 180 days, as well as the average daily gain from birth to 90 and 180 days) were collected on 334 Djallonke sheep including 140 females and 194 males over two consecutive generations in the Betecoucou Breeding Farm in Benin. The estimation of the heritability coefficients for the characters considered was performed by analysis of variance using the general linear model procedure through a mixed model. Analyses of variance revealed the significance of factors such as year, season and sex on birth weight (BWT), weaning weight (WWT) and average daily gain from birth to 90 days (ADG0- 90). The year*season interaction is significant for all dependent variables, with the exception of the body weight at 6 months (BOWT) and the average daily gain from 90 to 180 days (ADG90- 180). The heritability values estimated were 0.21 .007, 0.30 0.021, 0.29 0.030, 0.17 0.023 and 0.43 0.037 respectively for BWT, WWT, BOWT, ADG0 90 and ADG90-180. In the view of a genetic improvement program for Djallonke sheep, WWT and ADG90-180 could be used as selection criteria.
Keywords: Sheep; Djallonke; heritability; growth; Benin